Mapping fire regimes in China using MODIS active fire and burned area data. (August 2017) - Chen, Dongmei; Pereira, José M.C.; Masiero, Andrea; Pirotti, Francesco
Abstract: Relatively little is known about vegetation fire regimes in China. In this study, we investigated fire regime characteristics and their potential drivers, utilizing information extracted from the MODerate resolution Imaging Spectrometer (MODIS) satellite. Twelve fire regime variables were selected and computed on a regular grid over all of China, using MODIS burned area and active fire data during the period 2001 to 2016, to identify fire incidence and its inter-annual variability, seasonality, intensity, fire size distribution and vegetation types affected by fire. The variables were normalized and clustered to define six fire regimes with distinctive fire attributes. Results show that 78.6% of the land in China was affected by fire during the study period. The barren or sparsely vegetated lands of western China are nearly fire-free. Active fires were observed in Central China, but area burned was not detectable from MODIS. Forest fires in northeastern China are relatively large, infrequent, with a short fire season that peaks in non-winter seasons and higher inter-annual variability, implying a high likelihood of accidental causes. In contrast, forest fires in southern China are relatively small, frequent, with a long fire season that peaks in non-summer seasons, and lower inter-annual variability, suggesting regular use as a land management tool. Low inter-annual variability and low fire intensity were associated with cropland fires, whereas grassland fires generally exhibit the opposite traits. We have also discussed the potential drivers of each fire regime characteristics. Graphical abstract: Highlights: The study developed a new classification of fire regimes in China. Combing burned area and active fire data identified six distinct fire regimes. Forest fires in NE and S China display contrasting fire patterns. Large, intense and irregular fires occur in NE and SW mountains. Frequent, regular and unequally sized cropland fires occur in NE and E China.